Self-Identification as a STEM Person: A Gender Study among Secondary Students - Putri, Febi; Munfaridah, Nuril; Purwaningsih, Endang (Cahaya Smart Nusantara, 2025)
This study aims to compare self-identification as a Science, Technology, Engineering, Mathematics (STEM) person based on the gender of high school students. This study used a quantitative comparative research method. Data were collected through a survey about self-identification as a STEM person (N = 344), which was supported by observational data on student behavior in one class during physics lessons for seven meetings. The instrument used in this research was a questionnaire based on the STEM identity framework, which included interest (2 items), recognition (4 items), and performance-competence (6 items). Data were analyzed through means and independent samples t-tests. The results showed that there was no significant difference between male and female students in identifying themselves as STEM person. The average score for male students is 38.36, and for female students is 38.11. Based on the different test values, it was found that the [t = 0.369; p = 0.713 > 0.05] strengthened that there was no gender difference in identifying as a STEM person. However, the observation’s data indicated that male students tend to be more recognized by others (i.e., peers) in terms of understanding STEM subjects, such as mathematics and science. The findings of this study unboxed the silence on the issue of gender stereotypes in Indonesia, especially in the field of self-identification as a STEM person. More explorations are needed to construct a comprehensive understanding of reducing inequality in education, especially the issue of gender stereotypes in the context of science.